2,3,5-tryphenyltetrazolium chloride (TTC)as electron acceptor of culturable soil bacteria, fungi and actinomycetes - Praveen-Kumar; Tarafdar, J.C.
Dehydrogenase assays based on the reduction of 2,3,5- triphenyltetrazolium chloride (TTC)to the creaming red-coloured formazan (TPF), have been used to determine microbial activity in soil. By spraying TTC on culturable microbial colonies, whose growth was induced by applying glucose, we observed that from 72 to 100
Keywords: ACTINOMYCETES; BACTERIA; DEHYDROGENASE ACTIVITY; ELECTRON ACCEPTOR; FUNGI; TTC